ANALISIS JUMLAH DANA DESA MENGGUNAKAN METODE REGRESI LINEAR SEDERHANA - Imro’atun Najiyah; Ahmad Khairul Umam (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2021)
According to (Undang-Undang, 2014) “a village” is a village and traditional village. “a village” is a legal community unit that has territorial boundaries that are authorized to regulate and manage government affairs, the interests of the local community based on community initiatives, rights of origin, and/or traditional rights that are recognized and respected in the system of government of the Unitary State of the Republic of Indonesia. This article discusses total of village funds from village original income and transfer income in 2018, 2019 and 2020 in Weru Village, Paciran, Lamongan. We use Simple Linear Regression method. The data analysis technique is quantitative descriptive. It will describes and interprets an object or phenomenon by using numbers. From results, a simple linear regression equation is with correlation that means the correlation is not significant. And then, Calculation of and results that . It means that Ha (Hypothesis) is rejected. So, it can be concluded that the relationship between village original income and transfer income to the total of village funds has not significant effect.